Phonological Memory And Phonological Awareness In Children: A Meta-Analysis - Rexsy Taruna (Poltekkes Kemenkes Surakarta, 2022)
Background: Phonological memory skills have been widely documented to have an effect on phonological awareness performance, but with varying effect sizes. This meta-analysis aims to determine the summary effect size as a reference when considering phonological awareness interventions. Methods: For identification and selection of articles involved in this study, refer to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The database used to search for articles in PubMed. The inclusion criteria used in this study were articles published from 2013 to 2022, free full-text, and the subjects involved in the study did not have neurodevelopmental disorders. Results: Twelve articles were involved in data synthesis. The average sample in the study ranged from 4 years 2 months to 9 years 8 months. Ninety-one percent of the articles used a norm-referenced test to measure phonological memory abilities, while 66.6% used a norm-referenced test to measure phonological awareness abilities. The summary effect size on the relationship between phonological memory and phonological awareness is 0.433 (p <0.001). Conclusion: Professionals should consider the level of phonological memory ability in phonological awareness interventions.